Sesamol‐based terpenoids as promising bio‐sourced crop protection compounds against the wheat pathogen Zymoseptoria tritici. Issue 5 (21st January 2021) - Damiens, Audrey; Alebrahim, Mohammad Taghi; Léonard, Estelle; Fayeulle, Antoine; Furman, Christophe; Hilbert, Jean‐Louis; Siah, Ali; Billamboz, Muriel
Abstract: BACKGROUND: Research into environmentally friendly alternatives to conventional plant protection products, to promote sustainable agriculture and healthy food, is strongly encouraged. RESULTS: In this context, 20 naturally occurring terpenoids and phenolic compounds were selected and evaluated in vitro as crop protection compounds against Zymoseptoria tritici, the causal agent of Septoria tritici blotch of wheat. After selection of the most active compounds, some hemisynthetic modifications were conducted to modify their lipophilicity. These modifications led to the discovery of sesamol esters as promising antifungal agents, with IC50 around 10 μg/mL and a total absence of cytotoxicity against human cells. CONCLUSION: These sesamol‐based derivatives should be selected for further evaluations in planta to validate their use as wheat crop protection agents. Moreover, the importance of a balanced hydrophily/lipophilicity ratio should be further studied. © 2021 Society of Chemical Industry Abstract : Sesamol‐based derivatives emerged as promising bio‐based safe crop protection compounds towards the wheat pathogen Zymoseptoria tritici . A clear correlation between lipophilicity and activity was observed.